PERSONAL NETWORKS ON THE LABOUR MARKET: WHO FINDS A JOB IN THE CREATIVE SECTOR IN POZNAŃ? - Męczyński, Michał (Quaestiones Geographicae, 2016)
The spread of urban policies based on a set of standardised ‘creative city’ strategies has been criticised on a number of counts. In Scott’s (2006: 11) view, focusing just on “creating a high-quality urban environment, rich in cultural amenities and conducive to diversity in local social life” is too limited. He points out that the relationship between the presence of creative people and the development of a city is far more complex. The research undertaken as part of the European ACRE project (Accommodating Creative Knowledge: Competitiveness of Metropolitan Regions within the Enlarged Union) has revealed that access to a diversity of creative-labour-market opportunities is vital to both attract and retain talent in the longer term. Accessible and inclusive networks of creative workers are also vital, but their importance is often overlooked. The functionality of such networks has a huge impact on the possibility of finding a new job, and can be particularly important for lowering entry barriers for newcomers in creative occupations. Here, these issues are explored on the basis of a research conducted among managers of creative firms and international creative-class migrants in Poznań (Poland). This city has recently experienced major economic restructuring and a shift from the manufacturing industry towards a more creative and knowledge-based one.